Acoustic Monitoring of Tidal Flow and Salinity in a Tidal Channel - Hiep Thi Nguyen; Kiyosi Kawanisi; Mohamad Basel Al Sawaf (Journal of Marine Science and Engineering, 2021)
Fluvial Acoustic Tomography (FAT) is a powerful hydroacoustic system used in the investigations of estuarine dynamics. This research was designed to explore the effectiveness of using a novel and promising method of monitoring the continuous salinity intrusion and velocity distribution in a tidal channel using the FAT scheme. Four FAT units were installed near the riverbanks using a new zigzag system in a rectangular tomographic domain of 700 m × 170 m. The water velocities and salinities measured by FAT in this study were comparable to the data captured by traditional methods, including moving-boat Stream–Pro ADCP, CTD, and CT sensors. It was found that the delays in time between the maximum salinity and high water level along the channel ranged from 12 min to 1.5 h, with these time lags increasing seaward, primarily due to changes in freshwater flows upstream. In addition, the longitudinal salinity gradient was found to decrease toward the mouth of the river, with tide-driven mechanisms most likely being dominant in the dispersion process. The estuary is ebb-dominant, with an asymmetry in the ebb-tide and flood-tide velocities and the highest velocities occurring during the ebb tide. Furthermore, the residual current was found to be affected primarily by the freshwater discharge from upstream.